Dynamic Response of a 100,000 m3 Cylindrical Oil-Storage Tank under Seismic Excitations: Experimental Tests and Numerical Simulations - Honghao Li; Wei Zhao; Wei Wang (Shock and Vibration)
Considering the disastrous consequences of the oil tank failure, it is of great importance to ensure the safety of the large-scale oil tank under earthquakes. This study sheds light on investigating the dynamic response of a prototype 100,000 m3 cylindrical oil-storage tank under various seismic excitations. The foundation of the tank is also considered in this study so that the obtained results are closer to the reality. Shaking table tests are conducted using a 1/20 scale liquid-tank-foundation system under various seismic excitations. The test results reveal that the dynamic responses such as accelerations and the deformation of the test specimen in the major and minor vibration directions do not differ significantly. Finite element models are constructed for the test specimen and the prototype tank and are validated through comparing the simulation results with the test data. The simulation results suggest that it might be necessary to stiffen the locations on the tank wall where the thickness of the tank wall changes because the stresses at such locations may be close or even exceed the yield strength of the structural steel under severe earthquakes.